Antimicrobial properties of silver/graphene oxide nanocomposite prepared by redox chemical reaction - Leyva Gonzalez, Maria Elena; Ribeiro Rodrigues, Rosana; dos Santos, Igor Luiz; Oliveira, Adhimar Flávio; Tavares Wanderley Neto, Estácio; Nakagomi, Fabio; Marques, Paulo Sergio; Tavares , Eder do couto (Journal of Applied Materials and Technology, 2024)
Silver nanoparticles (AgNPs) exhibit outstanding antimicrobial properties, making them highly valuable in biomedical applications. This study presents the synthesis of a graphene oxide-silver nanoparticle (GO-Ag) nanocomposite via a redox chemical reaction, where the hydroxyl groups reduced silver ions present in graphene oxide (GO). Graphene oxide was obtained through electrochemical exfoliation of graphite, followed by ultrasonic exfoliation in the presence of silver ions to form GO-Ag. The materials were characterized using ultraviolet-visible (UV-Vis) spectroscopy, Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, scanning electron microscopy (SEM), and X-ray diffraction (XRD). UV-Vis, FTIR, and Raman spectra confirmed GO synthesis. In contrast, XRD and UV-Vis spectra verified the presence of silver nanoparticles in GO-Ag by detecting the surface plasmon resonance (SPR) band and silver’s characteristic diffraction peaks. SEM analysis showed the successful formation of silver nanoparticles on GO sheets. The disc diffusion method assessed Antimicrobial activity against Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative). GO-Ag nanocomposite displayed significant antibacterial activity, as evidenced by the formation of inhibition zones, whereas GO alone showed no antimicrobial effect. The enhanced antibacterial properties of GO-Ag are attributed to the synergistic interaction between GO and AgNPs. The increased surface area of silver nanoparticles further enhances their antibacterial effectiveness by facilitating better interaction with bacterial membranes. These findings highlight GO-Ag’s potential for use in antimicrobial coatings, wound dressings, and biomedical devices. This study demonstrates an effective, environmentally friendly approach to synthesizing antimicrobial nanocomposites, paving the way for their application in various medical and industrial fields.